Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1932296814540870
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Risk of Hypoglycemia Associated With Intravenous Insulin

Abstract: SymposiumThe level of glycemic control needed to improve outcomes without increasing the risk of hypoglycemia in hospitalized patients with critical illness is controversial. Achieving reasonable control of blood glucose without causing an excess risk of hypoglycemia is especially challenging in patients with ESRD, a condition commonly encountered in the critically ill.In 2001, Van den Berghe and colleague's landmark study in a surgical intensive care unit (ICU) suggested that strict blood glucose (BG) control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Eine Hyperglykämie und Glukosevariabilität scheint nicht im Zusammenhang mit erhöhten Mortalitätsraten bei Diabetespatienten im Vergleich zu Nichtdiabetespatienten zu stehen [468][469][470]. Patienten mit Diabetes, chronischer Hyperglykämie und Niereninsuffizienz im Endstadium könnten höhere Blutzuckerwertebereiche benötigen [471,472]. Begründung.…”
Section: N Sedierung Und Analgesieunclassified
“…Eine Hyperglykämie und Glukosevariabilität scheint nicht im Zusammenhang mit erhöhten Mortalitätsraten bei Diabetespatienten im Vergleich zu Nichtdiabetespatienten zu stehen [468][469][470]. Patienten mit Diabetes, chronischer Hyperglykämie und Niereninsuffizienz im Endstadium könnten höhere Blutzuckerwertebereiche benötigen [471,472]. Begründung.…”
Section: N Sedierung Und Analgesieunclassified
“…According to the studies carried out, the computerized protocols that are used for intensive glycemic control, are considered expensive, but effective in preventing hypoglycemia, in addition to optimizing the time spent by the nursing professionals. 16,17 The studies carried out comparing paper protocols and computerized protocols, unanimously highlighted the occurrence of decreased hypoglycemic events in intensive care units and even non-intensive ones that adopted computerized protocols. The computer alert system concerning the behavior of the nursing team, where it has numerous demands and in a tense sector, allows the team to establish priority in care when the alert goes off.…”
Section: Computerized and Non-computerized Technologies Used During Continuous Infusion Of Insulinmentioning
confidence: 99%
“…Among them, the calculations that must be made hourly at the bedside, delays or failure to perform blood glucose measurements and the difficulty in interpreting the protocols, these factors increased the variability of glycemic values and hypoglycemic events occurred more frequently. 16 In another study that evaluated nursing satisfaction with the use of paper protocols and computerized protocols, obtained a result of nurses' satisfaction using computerized protocols. Still in this study, it was observed that the nursing team deviated from what was required by the protocols, this could be assessed when comparing the insulin infusion doses that were found in the medical records and the doses that should really be included according to what was requested in protocols, so when compared to paper protocols, the computerized protocols suffered less deviation by the nursing team.…”
Section: Computerized and Non-computerized Technologies Used During Continuous Infusion Of Insulinmentioning
confidence: 99%
“…It is recommended that during IV insulin infusion, in the presence of chronic kidney disease (CKD), there should be conservative BG goals and insulin infusion rates [17,36,100,101]. Exogenous insulin bypasses first pass hepatic extraction, which is normally responsible for removal of about 40-60% of endogenously secreted insulin.…”
Section: Define Modifications In the Presence Of Worsening Renal Function Or Chronic Kidney Diseasementioning
confidence: 99%
“…The renal contribution to gluconeogenesis may be compromised. In the critical care setting, renal failure increases the risk for hypoglycemia during insulin therapy [5,17,22,36].…”
Section: Define Modifications In the Presence Of Worsening Renal Function Or Chronic Kidney Diseasementioning
confidence: 99%